(untitled) (Journal of Enam Medical College, 2013)
Background: To evaluate gastrointestinal pathology in computed tomography (CT) scan, optimum distention, mural visualization and gastrointestinal tract discrimination are necessary. High attenuation oral contrast material in the form of iodine solution has drawbacks in mural visualization and tolerance. Milk can be used as a low attenuation CT oral contrast agent in gastrointestinal tract discrimination and mural visualization with better tolerance. Objective: The purpose of our study was to compare the effectiveness, cost, and tolerance of milk and iopamiro (iodinated positive contrast medium) in patients undergoing abdominal CT with oral and IV contrast media. Materials and Methods: Two hundred and twelve patients were purposively assigned to receive either whole milk (n = 110) or iopamiro (n = 100). Results were independently reviewed by radiologists. Degree of bowel distention, mural visualization and gastrointestinal tract discrimination were qualitatively scored on a 4- point scale. A questionnaire regarding oral contrast tolerability was provided to each patient. Cost comparison of the two agents was performed. Results: No statistically significant differences were seen between whole milk and iopamiro with respect to degree of bowel distention and gastrointestinal tract discrimination for all segments of bowel studied (p > 0.05). Mural visualization is better with whole milk compared with iopamiro (p < 0.05). Significantly more patients ranked milk as pleasant in taste compared with iopamiro (p < 0.05). Milk was better tolerated than iopamiro, with fewer gastrointestinal side effects, including abdominal discomfort (p = 0.065), cramping (p = 0.309), nausea (p = 0.001), vomiting (p = 0.003) and diarrhea (p = 0.347). The cost per patient for iopamiro is 900 BDT compared with 60 BDT for milk. Conclusion: Whole milk is comparable to iopamiro with respect to bowel distention and gastrointestinal tract discrimination and better in bowel wall visualization and has better patient acceptance, and fewer adverse symptoms. Milk is a costeffective alternative to iopamiro as a low-attenuation CT oral contrast agent. Journal of Enam Medical College; Vol 3 No 2 July 2013; Page 71-76 DOI: http://dx.doi.org/10.3329/jemc.v3i2.16126